Whole genome resequencing reveals the correlation between selection signatures and adaptability of Micropterus salmoides to artificial fed - Tao Zhu; Jinxing Du; Hongmei Song; Caixia Lei; Yingshen Cen; Chenghui Wang; Shengjie Li (Scientific Reports)
Abstract Largemouth bass (Micropterus salmoides, LMB) is an important aquaculture species due to its excellent flesh quality and environmental adaptability. It has been continuously introduced to many countries and cultured for decades. Here, an LMB population was used for selective breeding to improve growth rate and feed adaptability. After five generations of breeding, the growth rate improved by 38%, and feed adaptability improved by 22% compared to the non-breeding population. To study the underlying genetic mechanism, 100 LMB from the breeding population and 100 from the non-breeding population were sampled for whole-genome resequencing. The population genetics analysis shows that the breeding population has a higher inbreeding coefficient and linkage disequilibrium (LD) level, a lower nucleic acid diversity and effective population size (Ne). Using $$F_{ST}$$ (fixation index), we found that the average $$F_{ST}$$ value between the two populations was 0.07, with the highest $$F_{ST}$$ value reaching 0.38, which overlaps with the trypsin gene. Additionally, other genes exhibiting high $$F_{ST}$$ values are associated with functions such as neural development, glucose metabolism, and growth. Using $$F_{ST}$$ and nucleic acid diversity as criteria, we identified 698 genes that are positively selected in the breeding population, and gene functional enrichment analysis shows that 36 genes are related to the olfactory receptor pathway. Overall, our study found that multiple genes were selected in the LMB breeding population. These genes may be associated with adaptation and digestion of artificial feed in fish.